Perancangan Sistem Informasi E-Catalogue Berbasis Website Menggunakan Metode Waterfall - Jonatan Maruli Butarbutar; Darmansah Darmansah; Rona Nisa Sofia Amriza (Universitas Budi Darma, 2022)
The problem faced by CV. Ramos Ponsel is that competitors have just started the same business as Cv. Ramos Ponsel, so that it has the impact of decreasing consumers in meeting their needs at Cv. Ramos Ponsel. With the situation for the store to innovate in customer service. The innovations in question are, among others, digitizing business processes based on a website, one of which is using an electronic catalog. The purpose of this research is to produce an E-Catalogue that can support the business processes of CV. Ramos Ponsel. The method used in this research is the Waterfall method. Waterfall every step of the work process is completed first to move to the next stage. The Waterfall Stage itself consists of Planning, Analysis, Design, Implementation, Testing, and Maintenance/Maintenance. With the existence of an e-catalogue that is designed to have superior value than e-catalogue owned by other institutions, by adding features that benefit sellers and buyers in the business process. The result of this research is to produce an E-Catalog information system on Cv. Ramos Mobile based web site.